A latency fractional order model for HIV dynamics - Pinto, Carla M.A. (2017)
We study a fractional order model for HIV infection where latent T helper cells are included. We compute the reproduction number of the model and study the stability of the disease free equilibrium. We observe that the reproduction number varies with the order of the fractional derivative α. In terms of epidemics, this suggests that varying α induces a change in the patients’ epidemic status. Moreover, we simulate the variation of relevant parameters, such as the fraction of uninfected CD4+ T cells that become latently infected, and the CTLs proliferation rate due to infected CD4+ T cells. The model produces biologically reasonable results.